Duodenal rather than antral motility contractile parameters correlate with symptom severity in gastroparesis patients. Issue 3 (17th December 2014) - Barshop, K.; Staller, K.; Semler, J.; Kuo, B.
Abstract Background Studies of symptomatic gastroparetics consistently find poor correlation with gastric emptying. We hypothesized that concomitant small bowel dysmotility may play a role in symptom causation in gastroparesis and sought to test this hypothesis by using wireless motility capsule (WMC) testing to simultaneously measure antral and duodenal area under pressure curve (AUC) in patients with delayed gastric emptying. Methods Using a cohort from a multicenter clinical trial and a separate tertiary clinical database, we identified gastroparetics that underwent concurrent WMC testing and completed the Gastroparesis Cardinal Symptom Index, a validated questionnaire. Our study included 35 gastroparetics defined by a gastric emptying time (GET) ≥5 h. Antral and duodenal AUC were assessed at 1‐h windows pre‐GET and post‐GET, respectively. Key Results We found moderate correlations between duodenal AUC and symptom severity in the combined cohort (n = 35; R = −0.42; p = 0.01; 95% CI −0.7, −0.1). Removing patients with colonic delay resulted in a stronger correlation of duodenal AUC to symptom severity (n = 21; R = −0.63; p < 0.01; 95% CI −0.81, −0.31). The multicenter trial (n = 20) and clinical practice cohorts (n = 15) had significantly different symptom severity and exclusion criteria. When analyzed separately, significant correlations between duodenal AUC and symptom severity were observed (R = −0.71; p < 0.01; 95% CI −0.9, −0.4 and R = −0.72; p < 0.01; 95% CI −0.9, −0.3, respectively). Symptom severity and antral motility showed no correlation. Conclusions & Inferences We found significant correlations between duodenal AUC and symptom severity in two cohorts of gastroparetics. Small bowel motility may contribute to symptom generation in gastroparetic patients and this may inform therapeutic considerations.